Petrogenesis of highly fractionated I-type granites in the Zayu area of eastern Gangdese, Tibet: Constraints from zircon U-Pb geochronology, geochemistry and Sr-Nd-Hf isotopes - Zhu, DiCheng; Mo, XuanXue; Wang, LiQuan; Zhao, ZhiDan; Niu, Yaoling; Zhou, ChangYong; Yang, YueHeng (Science China. Earth sciences, 2009)
The Cretaceous granitoids in the middle and northern Gangdese, Tibet are generally interpreted as the products of anatexis of thickened deep crust genetically associated with the Lhasa-Qiangtang collision. This paper reports bulk-rock major element, trace element and Sr-Nd isotopic data, zircon U-Pb age data, and zircon Hf isotopic data on the Zayu pluton in eastern Gangdese, Tibet. These data shed new light on the petrogenesis of the pluton. Our SHRIMP zircon U-Pb age dates, along with LA-ICPMS zircon U-Pb age dates recently reported in the literature, indicate that the Zayu pluton was emplaced at about 130 Ma, coeval with Early Cretaceous magmatic rocks in other areas of eastern Gangdese (e.g., Rawu, Baxoi areas) and the Middle Gangdese. The Zayu pluton samples lack amphibole and muscovite, and are compositionally characterized by high SiO2 (69.9%―76.8%), K2O (4.4%―5.7%), and low P2O5 (0.05%―0.12%). These samples also have A/CNK values of 1.00-1.05, and are enriched in Rb, Th, U, and Pb, and depleted in Ba, Nb, Ta, Sr, P, Ti, and Eu. These geochemical features suggest that the Zayu pluton samples are metaluminous to slightly peraluminous and are of highly fractionated I-type granite. The Zayu pluton samples have high εNd(t) values (-10.9--7.6) and low initial 87Sr/86Sr ratios (0.7120- 0.7179) relative to melts derived from mature continental crust in the Gangdese (e.g., Ningzhong Early Jurassic strongly peraluminous granite). The Zayu pluton samples are heterogeneous in zircon εHf(t) values (-12.8--2.9), yielding ancient zircon Hf crustal model ages of 1.4―2.0 Ga. The data obtained in this study together with the data in the recent literature suggest that the Early Cretaceous granitoids in eastern Gangdese represent the eastward extension of the Early Cretaceous magmatism in the middle Gangdese, and that the Lhasa micro-continent block with ancient basement may extend for ~2000 km from east to west. Zircon Hf isotopic data and bulk-rock zircon saturation temperature (789-821℃) indicate that mantle-derived materials likely played a role in the generation of the Zayu pluton. We propose that the Zayu pluton was most likely generated in a setting associated with southward sub- duction of the Bangong-Nujiang ocean floor, where mantle wedge-derived magmas may have providedthe heat and material for the anatexis of ancient crust of the Lhasa micro-continent, resulted in hybrid melts (i.e., mantle-derived basaltic magmas + crust-derived felsic magmas). Such hybrid melts with subsequent fractional crystallization are responsible for the highly evolved Zayu pluton (crust thick- ening is not a prerequisite).